On Interval-Separable Subsets of Vertices of a Complete Graph - Arakelyan, Hakob Z.; Kamalian, Rafayel R. (Mathematical Problems of Computer Science, 2021)
A subset R of the set of vertices of a graph G is called interval-separable if there exists a proper edge coloring of G in which colors of edges incident with any vertex x of G form an interval of integers if xR . All interval-separable subsets of the set of vertices of the complete graph are found.